2 - Communication and Conflict: A Commentary on the Role of the Media - Chinyere Stella Okunna, (Africa Media Review, 2004)
In this commentary, the author argues that conflict is irresistible to the mass media. The editorial content of both print and electronic media, she says, demonstrate this strong appetite. However, while media practitioners have a duty to report conflict situations as they see them, the author insists that they also have a responsibility to enhance the opportunities for peaceful resolution of conflicts.